Adsorption of gallic acid in aqueous solution by Amberlite XAD-7 - Abdul Muiz, Aziz (Universiti Sains Malaysia, 2009)
The adsorption behaviour of gallic acid onto XAD-7 was studied to determine the effects of pH, contact time, temperature, concentration of gallic acid and amount of XAD-7. The adsorption capacities were strongly influenced by the solution pH where the optimum working pH was found to be at pH 2.0. The shaking time (45 min) was found suitable for maximum adsorption. The batch equilibrium data were correlated to Langmuir and Freundlich isotherm and the data fitted better to the langmuir isotherm. The thermodynamic parameters were calculated and the corresponding value showed that the adsorption of gallic acid onto XA0-7 was spontaneous, entropy-driven and endothermic.